High-level OIMS structure - Kruseman, Gideon (2023)
This JSON code presents the high-level structure of any OIMS-compatible metadata file. OIMS is the Open Ontology-based Interoperable Information Asset Metadata Schema, a flexible and extensible metadata schema designed to standardize and organize metadata for various information assets like datasets, documents, models, and publications, making them more accessible, transparent, and reusable.